Corrected Analysis of the Effect of Preparation Parameters on Leakage in Liquid Surfactant Membrane Systems - Pfeiffer, R. M.; Bunge, A. L.; Cheung, H. M.; Shere, A. J. (Separation science and technology, 1992)
The phenomenon of encapsulated phase leakage is an important consideration in liquid surfactant membrane extraction proceses. In previous reports, values of leakage as a function of time and several formulation and operating variables were given. Unfortunately, these data analyses contain an error which significantly affects the conclusions. In this article, a reanalysis of the experimental data obtained by Shere and Cheung is performed. Much higher values of leakage are observed than reported earlier. Also, for the time duration of the leakage experiments, there is no basis for identifying a final, limiting leakage value. Further, each of the parameters studied and many of the two way interactions did influence leakage.